Understanding China’s System for Addressing Legislative Conflicts: Capacity Challenges and the Search for Legislative Harmony - Hand, Keith J. (Columbia Journal of Asian Law, 2013)
While the rapid adoption of legislation has played an important role in advancing China’s reform agenda, it has also produced a large number of legislative conflicts. This legislative disorder has posed challenges for China’s economic and legal modernization efforts. China addresses legislative conflicts primarily through a system of filing and review of legislation at different levels of government. Despite the severity of China’s legislative disorder, state organs with formal authority to annul or amend conflicting lower-level legislation rarely if ever exercise this authority. Citizens enjoy the right to raise proposals for the review of legislative conflicts, but central filing and review organs never respond to these proposals. On the other hand, the people’s courts, which have no formal authority to review legislation, engage in a form of limited judicial review when they choose the legislation to apply in individual cases. To explain such phenomena, we must recognize that the core problem shaping the design and operation of the filing and review system is a multidimensional problem of capacity. Legislative institutions have accommodated limited judicial review of legislation and empowered citizens to raise review proposals primarily because they lack the capacity to carry out their basic functions. These mechanisms should be understood as components of an integrated, multilayered system for supervising legislation. Understanding China’s system in this way reveals both likely limitations and opportunities in future reform efforts. Reforms are more likely to succeed if they acknowledge core capacity limitations, take account of existing patterns of institutional interaction, and effectively leverage the roles of courts and citizens to improve the capacity of the system as a whole. Specifically, reformers should explore ways to strengthen communication links between filing and review. organs and people’s courts, encourage citizens to raise concerns about legislative conflicts during the legislation drafting stage, and focus first on addressing conflicts involving lower-level legislation rather than on the sensitive and politicized issue of constitutional review.